Comparing water-level policies in a boreal reservoir: How wave and ice energy can help maintain walleye spawning habitat. (3rd July 2017) - Papenfuss, Jason T.; Cross, Tim; Venturelli, Paul A.
ABSTRACT: Papenfuss JT, Cross T, Venturelli PA. 2017. Comparing water-level policies in a boreal reservoir: how wave and ice energy can help maintain walleye spawning habitat. Lake Reserve Manage. 00:00–00. Water levels in reservoirs affect the timing and depth of wave and ice forces that help maintain walleye ( Sander vitreus ) spawning habitat. We studied how changes in a water-level management policy ("rule curve") in 2000 affected these forces on 3 lakes of the Namakan Reservoir, a large boreal reservoir on the border of Canada and the United States. The 2000 rule curve increased mean water levels (0.1 m) during open-water seasons and caused a significant increase in the amount of time each year that wave energy over suitable spawning substrates suspended <0.2 mm sediments at known spawning locations (6–18%, P < 0.01). Conversely, a decrease in the mean range (0.7 m) of water-level elevations during winter seasons caused an 11% decrease ( P < 0.01) in the interaction of ice with spawning substrates at known spawning locations. However, ice scour still affected those substrate elevations that were used frequently by walleye during typical spawning seasons. Our findings suggest that water-level management is important for maintaining suitable walleye spawning habitats, and that policies can be designed to optimize those habitat conditions.